Reliable: Resource allocation mechanism for 5G network using mobile edge computing - Pereira, Rickson S. [UNESP]; Lieira, Douglas D. [UNESP]; da Silva, Marco A. C.; Pimenta, Adinovam H. M.; da Costa, Joahannes B. D.; Rosário, Denis; Villas, Leandro; Meneguette, Rodolfo I. (MDPI, 2020)
Technological advancement is currently focused on the miniaturization of devices, and integrated circuits allow us to observe the increase in the number of Internet of Things (IoT) devices. Most IoT services and devices require an Internet connection, which needs to provide the minimum processing, storage and networking requirements to best serve a requested service. One of the main goals of 5G networks is to comply with the user’s various Quality of Service (QoS) requirements in different application scenarios. Fifth-generation networks use Network Function Virtualization (NFV) and Mobile Edge Computing (MEC) concepts to achieve these QoS requirements. However, the computational resource allocation mechanisms required by the services are considered very complex. Thus, in this paper, we propose an allocation and management resources mechanism for 5G networks that uses MEC and simple mathematical methods to reduce the model complexity. The mechanism decides to allocate the resource in MEC to meet the requirements requested by the user. The simulation results show that the proposed mechanism provides a larger amount of services, leading to a reduction in the service lock number and as a reduction in the blocking ratio of services due to the accuracy of the approach and its load balancing in the process of resource allocation.
Keywords: 5G; MEC; Resource allocation